Mixed Type Haemangioma of the Inferior Turbinate: A Rare Cause of Epistaxis - Penezić, Ana (Indian J Otolaryngol Head Neck Surg, 2016)
Haemangiomas of the nasal cavity are rare benign tumours which usually arise in the Kiesselbach triangle of the septum. Mostly they are seen in young population with peak age 20 years. Epistaxis is the most common symptom in these patients. We present a case of a 62-year-old woman with recurrent epistaxis. On examination she had had an obstruction of both nasal cavities. Computed tomography imaging demonstrated a well-defined tumour originating from the posterior tip of the right inferior turbinate, passing into the nasopharynx. The tumour was managed via endoscopic endonasal approach. The histological analysis revealed a tumour tissue with the appearance of a cavernous haemangioma as well as capillary haemangioma. A focus of intravascular endothelial papillary hyperplasia was also observed. In patients with endonasal benign tumours choice of surgical approach depends on the exact location of the tumour and suspected pathology. The transnasal endoscopic approach and bipolar cautery resection enable adequate exposure and visualization of the tumour, control of bleeding and complete removal of the tumour.